Impact of Tobacco Use on Lipid Metabolism in Adult Females: A Study from Erbil-Kurdistan Region of Iraq - Merza, Mohammed; Jabbar Jawhar, Huda; Sedeeq Ahmed, Azheen; Hiwa Hady, Roshna; Hwaiz, Rundk (Journal of Neonatal Surgery, 2025)
Background: Limited studies have explored the relationship between smoking and lipid profiles in adult female smokers. Materials and Methods: This study aimed to assess and compare the serum lipid profiles of adult female smokers with those of non-smoking females (control group). Serum lipid levels were measured in 200 female participants. Results: Among the participants, 110 were smokers and 70 were non-smokers (controls), aged between 25 and 50 years. Only smokers with a history of smoking for more than five years were included. The findings showed that the mean serum levels of total cholesterol (365.2 ± 42.2 mg/dl), triacylglycerol (206.4 ± 40.6 mg/dl), very low-density lipoprotein (42.2 ± 14.2 mg/dl), and low-density lipoprotein (146.2 ± 8.81 mg/dl) were significantly higher in female smokers compared to non-smokers, whose mean levels were total cholesterol (182.0 ± 28.2 mg/dl), very low-density lipoprotein (18.8 ± 8.2 mg/dl), triacylglycerol (96 ± 6.4 mg/dl), and low-density lipoprotein (84.54 ± 8.2 mg/dl). Conversely, the mean serum level of high-density lipoprotein cholesterol was lower in chronic female smokers (36.6 ± 2.6 mg/dl) compared to non-smokers (65.3 ± 8.0 mg/dl). Conclusion: The findings suggest that cigarette smoking in females leads to dyslipidemia, which increases the risk of cardiovascular disease.